2016
DOI: 10.3354/dao03084
|View full text |Cite
|
Sign up to set email alerts
|

Development of Streptococcus agalactiae vaccines for tilapia

Abstract: Vaccination is a widely accepted and effective method to prevent most pathogenic diseases in aquaculture. Various species of tilapia, especially Nile tilapia Oreochromis niloticus, are farmed worldwide because of their high consumer demand. Recently, the tilapia-breeding industry has been hampered by outbreaks of Streptococcus agalactiae infection, which cause high mortality and huge economic losses. Many researchers have attempted to develop effective S. agalactiae vaccines for tilapia. This review provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 58 publications
1
73
0
Order By: Relevance
“…It can stimulate organisms to induce effective cell‐mediated and antibody‐mediated immunity on the premise of avoiding pathogenicity and often provide lifelong immunity at low doses. Furthermore, live vaccines are relatively low cost and easy to apply (Frey, ; Liu et al, ). In order to develop attenuated bacteria via selection of resistance to chemicals, erythromycin was used in this study, and an erythromycin‐resistant S. agalactiae strain (TFJ‐ery) was isolated from the natural low‐virulence strain TFJ0901.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can stimulate organisms to induce effective cell‐mediated and antibody‐mediated immunity on the premise of avoiding pathogenicity and often provide lifelong immunity at low doses. Furthermore, live vaccines are relatively low cost and easy to apply (Frey, ; Liu et al, ). In order to develop attenuated bacteria via selection of resistance to chemicals, erythromycin was used in this study, and an erythromycin‐resistant S. agalactiae strain (TFJ‐ery) was isolated from the natural low‐virulence strain TFJ0901.…”
Section: Discussionmentioning
confidence: 99%
“…The marker (M) sizes were 2,000, 1,000, 750, 500, 250 and 100 bp, respectively. Lanes 1 and 2 were TFJ0901 and TFJ-ery, respectively Furthermore, live vaccines are relatively low cost and easy to apply (Frey, 2007;Liu et al, 2016). In order to develop attenuated bacteria via selection of resistance to chemicals, erythromycin was used in this study, and an erythromycin-resistant S. agalactiae strain (TFJery) was isolated from the natural low-virulence strain TFJ0901.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In 1966, GBS infection of fish was reported in the USA 2 with subsequent outbreaks described in fish farms in Asia and the Americas 3,4 . GBS infection is often associated with high levels of mortality in fish and with the worldwide growth of aquaculture has significant economic impact 5 . In the 1970s GBS was described as the leading cause of human neonatal infectious morbidity and mortality with two distinct GBS-associated syndromes: earlyonset disease occurring 0-6 days after birth and late-onset disease occurring 7 days -3 months after birth 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…| 1399 DU et al to study the pathogenesis of streptococcus in fish (Yamamoto et al, 1999). It has been reported that the main pathogens of tilapia infection are Streptococcus agalactiae and Streptococcus dolphinis (Liu et al, 2016). Another study reported that the main pathogen isolated from infected tilapia after 2008 was S. agalactiae (Lusiastuti, Textor, Seeger, Akineden, & Zschöck, 2014).…”
mentioning
confidence: 99%